Dari Pesantren untuk PIAUD - Binti Su'aidah Hanur; Fatimah Fatimah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Abstract: The width spreading of kindegarten school has given new insight toward education world. Although the early childhood education concept had been issued in the 14th century but the implementation has just been launched in the 21st century. The early childhood islamic education concept has too, although the concept had been existed in the 5th century but the implementation has been launched recently. This article tries to analyze the relevantion of Al- Ghazali concept toward the process of early childhood islamic education in the modern era which is seen from the teaching and the implementing points of view both at home and at school. When the goal of the education mainly islamic education related to the moral values does not match with the developmental period, the need and the characteristic of early childhhood, it will contribute the worst treatment for their future.Keywords: Islamic Education, Early Childhood, al-Ghazali